Translators and (lack of) power - a study of Danish company translators’ occupational status - Dam, Helle V.; Zethsen,, Karen Korning (Language at Work - Bridging Theory and Practice, 2009)
Translators’ occupational status has received very little attention as a research topic in its own right. However, when we go through the translation literature, we frequently come across references to translation as a low-status profession.